2014
DOI: 10.1371/journal.pone.0085935
|View full text |Cite|
|
Sign up to set email alerts
|

MSLN Gene Silencing Has an Anti-Malignant Effect on Cell Lines Overexpressing Mesothelin Deriving from Malignant Pleural Mesothelioma

Abstract: Genes involved in the carcinogenetic mechanisms underlying malignant pleural mesothelioma (MPM) are still poorly characterized. So far, mesothelin (MSLN) has aroused the most interest. It encodes for a membrane glycoprotein, frequently over-expressed in various malignancies such as MPM, and ovarian and pancreatic cancers. It has been proposed as a diagnostic and immunotherapeutic target with promising results. However, an alternative therapeutic approach seems to rise, whereby synthetic molecules, such as anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 29 publications
1
30
0
1
Order By: Relevance
“…To this end, different strategies, such as "suicide genes" (which make the tumor sensitive to certain drugs), administration of tumor suppressor genes, or the transfer of immunomodulatory genes to the pleural space have been proposed. [96][97][98][99] Results in the clinic are rather disheartening to date due to vector-related problems and relative inefficiency in controlling large tumor masses. However, gene therapy is most likely to be incorporated into the multimodal strategy, and when combined with nanotechnology techniques it will contribute very significantly to the improvement of treatment of malignant pleural mesothelioma in the future.…”
Section: Future Outlookmentioning
confidence: 99%
“…To this end, different strategies, such as "suicide genes" (which make the tumor sensitive to certain drugs), administration of tumor suppressor genes, or the transfer of immunomodulatory genes to the pleural space have been proposed. [96][97][98][99] Results in the clinic are rather disheartening to date due to vector-related problems and relative inefficiency in controlling large tumor masses. However, gene therapy is most likely to be incorporated into the multimodal strategy, and when combined with nanotechnology techniques it will contribute very significantly to the improvement of treatment of malignant pleural mesothelioma in the future.…”
Section: Future Outlookmentioning
confidence: 99%
“…For these purposes, the use of recombinant immunotoxins, monoclonal antibodies and T-cell therapy has been studied, all in potential combination with chemotherapy, as well as of antimesothelin vaccines or antibody-conjugates [46][47][48][49]. Most recently, gene-based targeted therapy considering mesothelin a key molecular target has been suggested [17]. Generally, it may be concluded that more recent studies suggest the use of SMRP levels as a suitable marker in association with the effectiveness of MM therapy and investigate the potential for further improvement of the diagnostic accuracy of SMRP levels by combining them with other markers.…”
Section: Discussionmentioning
confidence: 99%
“…In serum or pleural fluid, SMRPs may be determined by immunoenzymatic diagnostic assays, a very common example being Mesomark, as documented in numerous studies [13][14][15][16]. Although the role of mesothelin in normal and cancer cells still remains unclear [17], it has been suggested that mesothelin could be a factor promoting tumor invasion [18]. It has been shown that under normal circumstances, mesothelin is present in several human tissues, including the mesothelium and is aberrantly expressed mainly by MM but also by pancreatic cancer, ovarian cancer or some breast and lung cancers [7,12,19].…”
mentioning
confidence: 99%
“…The human mesothelioma cell line Mero-14 that has wild type p53 and expresses p53 protein (Additional file 17 : Figure S2) was used as a predicted wild type p53 source and was donated by Prof. Landi (University of Pisa) [ 36 ]. Mero-14 cells were cultured in Dulbecco’s Modified Eagle’s Medium (DMEM) (Sigma, UK) supplemented with 10% fetal bovine serum (Gibco, UK), and 1% penicillin/streptomycin (Lonza, USA) and maintained at 37 °C in a 5% CO 2 humidified atmosphere.…”
Section: Methodsmentioning
confidence: 99%